Lysosomal nanotoxicity: Impact of nanomedicines on lysosomal function - Uzhytchak, Mariia; Smolková, Barbora; Lunova, Mariia; Frtús, Adam; Jirsa, Milan; Dejneka, Alexandr; Lunov, Oleg (Advanced drug delivery reviews, 2023)
Although several nanomedicines got clinical approval over the past two decades, the clinical translation rate is relatively small so far. There are many post-surveillance withdrawals of nanomedicines caused by various safety issues. For successful clinical advancement of nanotechnology, it is of unmet need to realize cellular and molecular foundation of nanotoxicity. Current data suggest that lysosomal dysfunction caused by nanoparticles is emerging as the most common intracellular trigger of nanotoxicity. This review analyzes prospect mechanisms of lysosomal dysfunction-mediated toxicity induced by nanoparticles. We summarized and critically assessed adverse drug reactions of current clinically approved nanomedicines. Importantly, we show that physicochemical properties have great impact on nanoparticles interaction with cells, excretion route and kinetics, and subsequently on toxicity. We analyzed literature on adverse reactions of current nanomedicines and hypothesized that adverse reactions might be linked with lysosomal dysfunction caused by nanomedicines. Finally, from our analysis it becomes clear that it is unjustifiable to generalize safety and toxicity of nanoparticles, since different particles possess distinct toxicological properties. We propose that the biological mechanism of the disease progression and treatment should be central in the optimization of nanoparticle design.
Keywords: nanomedicína; Nanotechnology; lyzozomy; nanotechnologie; nanočástice; Nanoparticles; Lysosomes; Nanomedicine; Humans; lidé